Performance of Some Tree Species in Relation to Irrigation with Saline Waters - Jain, B L; Goyal, R S; Muthana, K D (Annals of Arid Zone, 2016)
Performance of different tree species under irrigation with waters of 2.7 to 9.0 mmhos electrical conductivity have shown variable effects on survival and growth. Adverse effects of high salinity in waters (9.0 mmhos) on survival and growth were observed in terms of high mortality and retardation in growth and collar diameter of Dichrostachys glomerata and Tamarix articulata. Survival and growth of Eucalyptus hybrid was adversely affected by water of 6.0 mmhos EC and Cassia siamea even with watersof2.7 mmhos EC. Survival and growth of Prosopis juliflora, Acacia aneura and Chenopodium species were not adversely affected even with waters of 9.0 mmhos EC. High salinity in irrigation waters caused increase in salinity levels of soils by 3-5 times and SAR values by 1.5 to 2 times. Salt concentrations and SAR values were lowered during rainy season.